Think good, feel good: a cognitive behavioural therapy workbook for children and young people - Paul Stallard (Hoboken, New Jersey : Wiley, 2019)
Newly updated edition of the highly successful core text for using cognitive behaviour therapy with children and young people The previous edition of Think Good, Feel Good was an exciting, practical resource that pioneered the way mental health professionals approached Cognitive Behaviour Therapy with children and young people. This new edition continues the work started by clinical psychologist Paul Stallard, and provides a range of flexible and highly appealing materials that can be used to structure and facilitate work with young people. In addition to covering the core elements used in CBT programmes, it incorporates ideas from the third wave CBT therapies of mindfulness, compassion focused therapy and acceptance and commitment therapy. It also includes a practical series of exercises and worksheets that introduce specific concepts and techniques. Developed by the author and used extensively in clinical practice, Think Good, Feel Good, Second Edition: A CBT Workbook for Children and Young People starts by introducing readers to the origin, basic theory, and rationale behind CBT and explains how the workbook should be used. Chapters cover elements of CBT including identifying thinking traps; core beliefs; controlling feelings; changing behaviour; and more. * Written by an experienced professional with all clinically tested material * Fully updated to reflect recent developments in clinical practice * Wide range of downloadable materials * Includes ideas for third wave CBT, Mindfulness, Compassion Focused Therapy and Acceptance and Commitment Therapy Think Good, Feel Good, Second Edition: A CBT Workbook for Children and Young People is a "must have" resource for clinical psychologists, child and adolescent psychiatrists, community psychiatric nurses, educational psychologists, and occupational therapists. It is also a valuable resource for those who work with young people including social workers, school nurses, practice counsellors, teachers and health visitors
Keywords: Behavior Therapy; Cognitive therapy for children; Cognitive Behavioral; Adolescent; Child